Rola świadomej zgody pacjenta w procesie diagnostyki i leczenia = The role of patient informed consent in the process of diagnosis and treatment - Podgórniak, Marta; Piróg, Marta; Putowski, Maciej; Padała, Olga; Zawiślak, Jacek; Sadowska, Monika; Morshed, Kamal; Smoleń, Agata (Journal of Education, Health and Sport, 2016)
Podgórniak Marta, Piróg Marta, Putowski Maciej, Padała Olga, Zawiślak Jacek, Sadowska Monika, Morshed Kamal, Smoleń Agata. Rola świadomej zgody pacjenta w procesie diagnostyki i leczenia = The role of patient informed consent in the process of diagnosis and treatment. Journal of Education, Health and Sport. 2016;6(4):103-114. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.49865 http://ojs.ukw.edu.pl/index.php/johs/article/view/3454 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.03.2016. Revised 10.04.2016. Accepted: 10.04.2016. Rola świadomej zgody pacjenta w procesie diagnostyki i leczenia Marta Podgórniak1, Marta Piróg1, Maciej Putowski1, Olga Padała1, Jacek Zawiślak1, Monika Sadowska2, Kamal Morshed3, Agata Smoleń3 1Studenckie Koło Naukowe przy Katedrze i Zakładzie Epidemiologii i Metodologii Badań Klinicznych, Uniwersytet Medyczny w Lublinie 2Pracownia Technik Diagnostycznych, Uniwersytet Medyczny w Lublinie 3Katedra i Zakład Epidemiologii i Metodologii Badań Klinicznych, Uniwersytet Medyczny w Lublinie Słowa kluczowe: świadoma zgoda, prawo medyczne, odpowiedzialność prawna. Streszczenie Zgoda pacjenta stanowi dokument wyznaczający zakres i warunki ingerencji personelu medycznego w sferę osobistą pacjenta, która jest chroniona na mocy konstytucji oraz innych aktów prawnych. Uzyskanie świadomej zgody od pacjenta odgrywa kluczową rolę w procesie diagnostyki i leczenia. Lekarz zobowiązany jest do uzyskania zgody na udzielenie świadczeń zdrowotnych mających na celu ratowanie życia oraz zachowanie, przywracanie lub poprawę zdrowia z wyłączeniem sytuacji, w których pacjent wymaga niezwłocznej interwencji medycznej. Celem pracy jest podsumowanie aktualnych przepisów dotyczących procesu pozyskiwania świadomej zgody od pacjenta. W przypadku wielu podstawowych świadczeń zdrowotnych wystarczająca jest zgoda werbalna. W przypadku świadczeń medycznych o podwyższonym ryzyku powikłań niezbędne jest pozyskanie zgody pisemnej, której treść powinna zawierać oświadczenie woli pacjenta (zgoda lub sprzeciw), określenie czynności medycznej i związanych z nią możliwych powikłań, które stanowią przedmiot zgody, podpis pacjenta oraz datę wyrażenia zgody. U osób poniżej 16 roku życia do podjęcia czynności medycznych niezbędna jest zgoda przedstawiciela ustawowego pacjenta małoletniego. W przypadku pacjenta, który ukończył już 16 rok życia wymagana jest zgoda zwana jako kumulatywna, czyli zgoda pacjenta oraz jego przedstawiciela ustawowego bądź faktycznego. Wykonywanie zabiegów i czynności diagnostyki laboratoryjnej bez zgody pacjenta jest dopuszczalne w pewnych wyjątkowych sytuacjach. W codziennej praktyce lekarskiej zachowanie poprawnej metodyki bywa zadaniem utrudnionym ze względu na ograniczoną ilość czasu lub trudności we współpracy z pacjentem, ocenie jego stanu świadomości oraz jednoznacznym rozwiązaniu kwestii nieuregulowanych prawnie. The role of patient informed consent in the process of diagnosis and treatment Marta Podgórniak1, Marta Piróg1, Maciej Putowski1, Olga Padała1, Jacek Zawiślak1, Monika Sadowska2, Kamal Morshed3, Agata Smoleń3 1Student Research Circle at the Department of Epidemiology and Clinical Research Methodology, Medical University of Lublin 2Diagnostic Techniques Unit, Medical University of Lublin 3Chair and Department of Epidemiology and Clinical Research Methodology, Medical University of Lublin Keywords: informed consent, medical law, legal liability. Abstract Patient’s consent is a document defining a range and terms of intervention of medical personnel in the patient's personal sphere, which is protected by the Constitution and other many laws. Obtaining consent to treatment from the patient plays a main role in the diagnosis and treatment. The doctor is obliged to obtain consent to provide health care services aimed at saving lives and preserving, restoring or improving the health with the exception of situations in which the patient requires immediate medical intervention. In the case of many basic health services verbal consent is sufficient. In the case of medical services with increased risk of complications it is necessary to get the written consent to treatment, the text should include a statement of the will of the patient, the term of medical activities and related possible complications, signature and the date of the patient's consent. For undertaking medical services in the group of people under 16 years it is necessary to get consent from patient's legal representative. In cases of a patients who are over 16 years it is needed to obtain the consent known as cumulative, that is the consent of the patient and his legal representative. Performing treatments and diagnostic activities without consent of the patient is permitted in certain exceptional situations. In daily practice of physicians, getting consent is sometimes difficult task due to the limited amount of time or difficulties in collaboration with the patient or assess his state of consciousness.